On Some Classes of Block Repetition Codes Over \(F_3+uF_3\), \(u^2=0\) and its Covering Radius of the Codes - Pandian, P. Chella (Journal of Informatics and Mathematical Sciences, 2024)
In this paper, to obtain the bounds for some classes of repetition codes with covering radius by using various weight and also the same size and different size of length in repetition codes over a finite ring \(R=F_3+uF_3\), \(u^2=0\).